2000
DOI: 10.1073/pnas.160128797
|View full text |Cite
|
Sign up to set email alerts
|

Specific binding sites for alcohols and anesthetics on ligand-gated ion channels

Abstract: Ligand-gated ion channels are a target for inhaled anesthetics and alcohols in the central nervous system. The inhibitory strychninesensitive glycine and ␥-aminobutyric acid type A receptors are positively modulated by anesthetics and alcohols, and site-directed mutagenesis techniques have identified amino acid residues important for the action of volatile anesthetics and alcohols in these receptors. A key question is whether these amino acids are part of an alcohol͞anesthetic-binding site. In the present stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
240
3

Year Published

2002
2002
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 243 publications
(257 citation statements)
references
References 26 publications
14
240
3
Order By: Relevance
“…As a mobile contact point between the LBD and TMD, the M2-M3 loop would have an important role in conformational transmission and gating, and this is not the first time that this has been suggested for Cys-loop receptors (67). In the simulation, the loop is seen to curl down into the hydrophobic pocket in the TMD, between M1, M2, and M3 where anesthetics are thought to bind to the receptor (68), and in other Cys-loop receptors such as the GABA receptor (69,70). For nicotinic channels, a view that anesthetics bind solely to M2 (71,72) seems to prevail.…”
Section: Conclusion and Discussionmentioning
confidence: 92%
“…As a mobile contact point between the LBD and TMD, the M2-M3 loop would have an important role in conformational transmission and gating, and this is not the first time that this has been suggested for Cys-loop receptors (67). In the simulation, the loop is seen to curl down into the hydrophobic pocket in the TMD, between M1, M2, and M3 where anesthetics are thought to bind to the receptor (68), and in other Cys-loop receptors such as the GABA receptor (69,70). For nicotinic channels, a view that anesthetics bind solely to M2 (71,72) seems to prevail.…”
Section: Conclusion and Discussionmentioning
confidence: 92%
“…There appears be a pocket located between TM2 and TM3 of the GABA A α subunit that binds both alcohols and anesthetics. It has been shown that within this pocket of the α 1 subunit, serine-270 and alanine-291 are essential not only for the binding of alcohols but also for alcohol-induced conformational changes within the GABA A receptor (Jung et al, 2005;Jung and Harris, 2006;Mascia et al, 2000;Mihic et al, 1997). However, these studies used very high concentrations of ethanol (200mM) that correspond to anesthetic concentration in vivo, and there is so far no evidence that ethanol binds to GABA A receptors at physiological doses.…”
Section: Gaba a Receptors: Structurementioning
confidence: 99%
“…A recent study suggests that neuroactive steroids contribute to the hypnotic effects of ethanol in rats (Khisti et al, 2003). Moreover, several studies (Mihic et al, 1997;Koltchine et al, 1999;Mascia et al, 2000;Ueno et al, 2001) have suggested that general anesthesia can be produced, at least in part, by enhancing neuronal inhibition mediated by the GABA A a-2 subunit.…”
Section: Subjective Effects Of Alcoholmentioning
confidence: 99%